Is there a generalized timing impairment in Autism Spectrum : Disorders across time scales and paradigms? - Isaksson, Sofia (fi=Turun yliopisto|en=University of Turku|, 2018)
Individuals with ASD have abnormal motor and perceptual functions that do not currently form diagnostic criteria of ASD, but nevertheless may affect everyday behaviour. Temporal processing seems to be one of such non-diagnostic yet impaired domains, although the lack of systematic studies testing different aspects of timing in the same sample of participants prevents a conclusive assessment of whether there is a generalized temporal deficit in ASD associated with diagnostic symptoms. 17 children diagnosed with ASD and 18 typically developing age- and IQ-matched controls carried out a set of motor and perceptual timing tasks: free tapping, simultaneity judgment, auditory duration discrimination, and verbal duration estimation. Parents of participants filled in a questionnaire assessing the sense and management of time. Children with ASD showed faster and more variable free tapping than controls. Auditory duration discrimination thresholds were higher in the ASD group than controls in a sub-second version of the task, while there were no group differences in a supra-second discrimination of intervals. Children with ASD showed more variable thresholds of simultaneity judgment, and they received lower parental scores for their sense and management of time. No group differences were observed in the verbal duration estimation task in the minute-range. Different timing functions were correlated in the ASD group but not among controls, whilst several timing measures correlated with ASD symptoms. We conclude that children with ASD show a broad range of abnormalities in temporal processing tasks including motor timing, perceptual timing, and temporal perspective.